LAJU FOTOSINTESIS JENIS-JENIS POHON PIONIR HUTAN SEKUNDER DI TAMAN NASIONAL GUNUNG HALIMUN-SALAK JAWA BARAT - Mansur, Muhammad (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2011)
Tree growth is closely related to the process of photosynthesis. So far the rate of photosynthesis in elements of secondary forests has not been known, especially in pioneer species. At the same height of the place and micro-climate conditions, the rate of photosynthesis of pioneer species of secondary forest has a different rate of photosynthesis. This study aims to determine the ability of the rate of photosynthesis of some secondary forest pioneer tree species in order to support reforestation efforts on degraded forests and at the same time looking for the kinds of pioneers who have a high absorption of CO2 gas in an effort to reduce global warming caused by emissions CO2 gas in the air. The survey results noted there are 6 common pioneer tree species grow at the sites. Trema orientalis had the highest CO2 assimilation value which is equal to 20,350 Î¼mol m-2s-1, followed by the Macaranga triloba (17,198 Î¼mol m-2s-1), Omalanthus populneus (14,097 Î¼mol m-2s-1), Mallotus paniculatus (13,118 Î¼mol m-2s-1), Macaranga tanarius (12,862 Î¼mol m-2s-1) and Weinmannia blumei (10,058 Î¼mol m-2s-1). Research conducted during the rainy season (September 2010). During measurement, the light radiation in the upper leaf surface between 63,583 to 363,750 Î¼mol m-2s-1, air temperature 21,8 to 26,70C, air humidity 75,8-89,8%, light intensity 2483,3 to 28701,7 Lux, soil pH 5,8 to 6,3 and soil moisture between 50,7 to 71,7%.